The Effect Of The Application Of Problem-Based Learning Model On Learning Outcomes In Ppkn Subjects For Class XI Students At MAN 2 Mataram - Adnin, Olyvia; Zubair, Muh.; Kurniawansyah, Edy; Ismail, M. (UNDIKMA, 2024)
Student learning outcomes are the result of changes in a person's behavior obtained during interaction with the environment which includes cognitive aspects, affective aspects, and psychomotor aspects. This study aims to determine the effect of applying the Problem-Based Learning model on the learning outcomes of grade XI students in Civics subjects. The research method used is a quantitative approach with the type of research quasi-experimental design and sampling through purposive sampling using two classes, as well as data collection through observation and multiple-choice tests. Based on the results of data analysis of the average class value, the experimental class average on the pretest was 68.03, and on the posttest was 82.29. In contrast, the control class obtained an average value on the pretest of 62.35 and the posttest of 69.62. Using the t-test calculation with the Paired Sample t-test formula at a significance level of 5% with a Sig value. (2-tailed) 0.000 <0.05 then Ha is accepted and Ho is rejected or the two population averages differ. This means that there is an effect of applying the Problem-Based Learning learning model on learning outcomes in Civics subjects for grade XI students at MAN 2 Mataram compared to only using conventional learning models